Counseling-based child-friendly school support to enhance teacher knowledge and understanding - Nurfi Laili; Ghozali Rusyid Affandi; Fitria Nur Hasanah (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
This paper describes the implementation of counseling procedures and the process of identifying problems among elementary school students. Counseling conducted by classroom teachers serves as one of the strategies to address common issues in schools that partner with community service programs. This study applies the community service method, utilizing training and role-playing techniques. The aim of this training is to enhance teachers' empathy and active listening skills, enabling them to identify student problems and conduct basic counseling procedures effectively. Introducing and practicing counseling techniques represents a tangible step in preparing competent human resources to assist students in resolving both academic and non-academic challenges. This paper highlights the importance of a counseling approach for classroom teachers, emphasizing its role in fostering closer relationships with students and supporting them in finding solutions to their problems. The outcomes of this community service initiative include improved knowledge and understanding among teachers regarding the concepts and practical applications of counseling for students and their parents.